Methodology Assessment and Ways to Improve the Efficiency of Complex Use of Wood Resources in the Forest Complex of Vietnam - Thi Nhan Nguyen (Управленческое консультирование)
The high importance of the forestry sector in social, economic and environmental spheres implies the need for continuous assessment of the level of efficiency of use of wood resources. The analysis of the current state, trends and patterns of the wood industry in Vietnam has shown its low efficiency . As apriority the development of the article proposed algorithm to improve the efficiency of complex use of wood resources of Vietnam , allowing to provide an in-depth analysis of the activities in this area and the development of promising areas of corrective action.